American fascists the Christian right and the war on America - Hedges, Chris 1956- (Free Press, 2007)
Includes the author's perspective on abortion, Antichrist, apocalyptic violence, Bible, religious broadcasting media, George W. Bush, Christian Right, Christians, conversion process, converts, creationism, democracy, Democratic Party, dominionism, education system, elections, Darwinʼs theory of evolution, fundamentalism, homosexuality, Islam, Jesus, Jews, lesbians, liberalism, love, male church leaders, cult of masculinity, secular media, moral certitude, Nazism, Rhetoric of persecution, poverty, racism, Rapture, Republican Party, Pat Robertson, Satan, science, secular humanism, sin, televangelists, terrorism, totalitarian movements, Trinity Broadcasting Network, universities, Ur-Fascism, war, women, etc.